1999
DOI: 10.1103/physrevd.59.074020
|View full text |Cite
|
Sign up to set email alerts
|

Vector meson dominance and the ρ meson

Abstract: We discuss the properties of vector mesons, in particular the 0 , in the context of the hidden local symmetry ͑HLS͒ model. This provides a unified framework to study several aspects of the low energy QCD sector. First, we show that in the HLS model the physical photon is massless, without requiring off field diagonalization. We then demonstrate the equivalence of HLS and the two existing representations of vector meson dominance, VMD1 and VMD2, at both the tree level and one loop order. Finally the S matrix po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(77 citation statements)
references
References 72 publications
(85 reference statements)
2
75
0
Order By: Relevance
“…The ρ mass, as defined by the real part of the propagator M ρ , is highly model dependent [35]. The complex pole, however, is a true invariant, as has been shown for several models [31]. One should also note the difference between M ρ and the "Higgs-Kibble" mass m HK (m [31] resulting from spontaneous symmetry breaking.…”
Section: Phenomenological Constraints On F π (S)mentioning
confidence: 99%
See 1 more Smart Citation
“…The ρ mass, as defined by the real part of the propagator M ρ , is highly model dependent [35]. The complex pole, however, is a true invariant, as has been shown for several models [31]. One should also note the difference between M ρ and the "Higgs-Kibble" mass m HK (m [31] resulting from spontaneous symmetry breaking.…”
Section: Phenomenological Constraints On F π (S)mentioning
confidence: 99%
“…A first such model which illustrates that loop dressing of the γ − ρ transition can accomodate pion form factor data is given in [21] ; quite recently, the same idea was developed up to a more refined comparison with experimental data up to the φ mass [32]. We note that it has been explicitly demonstrated that regular VMD and VMD1 are equivalent [31], as one would expect from corresponding fit results [16].…”
Section: Properties Of the One-loop Correctionsmentioning
confidence: 99%
“…In the energy region below 1 GeV the process e + e − → ηγ, η → 3π 0 is the only process with a significant cross section and multi-photon final state. In the φ-meson region there is a contribution from the process (4). Since this energy region is above the ωπ 0 production threshold, there is also a background from the process (5).…”
Section: Selection Of Events In the Decay Channelmentioning
confidence: 99%
“…However, further improvement of accuracy of these branching ratios measurements is still important for development of various phenomenological models -quark models, SU(3) based linear and non-linear sigma models and vector meson dominance models, [2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Up to inessential coefficients related with vector coupling constants and SU(3) breaking effects, we have [30] :…”
Section: Su(2) Breaking Within the Hls Modelmentioning
confidence: 99%